Stabilization of Tropical Fibrous Peat Using Ordinary Portland Cement and Additives - Kalantari, Behzad (2010)
One of the most troublesome of soft and organic soils is fibrous peat due mainly to their high compressibility, and their low shear strength. In this study, fibrous peat has been stabilized with ordinary Portland cement (OPC), as well as OPC and five different types of additives namely; polypropylene fibers, steel fibers, silica fume, blast furnace slag, and fly ash. Shallow and deep stabilizations have been studied to improve strengths, as well as to reduce compressibility of fibrous peat. For shallow stabilization of fibrous peat, strength evaluation tests (un-soaked and soaked) were unconfined compressive strength (UCS), and California bearing ratios (CBR), and for deep stabilizations were, consolidation undrained triaxial (CU), and Rowe cell consolidation tests. Three types of curing technique have been studied for their effectiveness, as well as their ease of applications in the field. Curing techniques were; moist curing, moist curing with surcharge load, and air curing. Curing periods used were continued up to 180 days. Based on the results obtained from various curing techniques, air curing technique was chosen to be used for the entire shallow stabilization process. Optimum dosage rates for polypropylene fibers, silica fume, blast furnace slag, and fly ash as additives to be used in the research either in shallow or deep stabilization was determined through UCS tests. In-order to examine the effectiveness of stabilization method used in the research in the field, fibrous peat with its field moisture contents has been used for stabilized samples. Also, in-order for shallow stabilization process to be more effective, stabilized samples were tested for their strength at their optimum moisture contents (OMC) found from compaction curves. For deep stabilization of fibrous peat deposits, precast stabilized columns were developed and tested for their effects to improve shear strength parameters, as well as reducing compressibility of fibrous peat. The process of making precast stabilized peat columns included mixing fibrous peat with a specified amount of OPC, (with or without additives) at their optimum moisture contents. Each type of mixture was then compacted in to molds and left to dry. When drying was completed, they were taken out of their molds and inserted in the pre-drilled holes within the undisturbed fibrous peat, and tested for their strength as well as their deformation through CU triaxial, and Rowe cell consolidation tests respectively. Precast stabilized peat columns that were made of hemic or sapric peats were also tried for their strengths and deformations evaluations as well. The columns were tested for their load bearing capacities in a larger scale test tank. Untreated fibrous peats as well as six different types of precast stabilized fibrous peat columns were tested in the test tank. As the curing period were increased, more strength obtained by the stabilized peat samples. Among various types of additives used in this research, the most effective dosage rates for polypropylene fibers was found to be 0.15%, and for silica fume 10, and 5% when lower amount of OPC (< 25%) and higher amount of OPC (> 25%) were used respectively. As the amount of steel fibers increased from 2 to 4% in the OPC treated samples, the stabilized samples gained further strength. Joint uses of polypropylene and steel fibers, use of polypropylene fibers, and use of silica fume in OPC treated fibrous peat provide the highest strength during curing period respectively. Use of blast furnace slag and fly ash as chemically active additives to stabilize fibrous peat were positive but the degree of effectiveness was not as effective as when OPC alone was used. Test results in this study indicate that, stabilization procedures used in either shallow (mass), or deep stabilization improve the load bearing capacities of untreated fibrous peat by increasing its load bearing capacity, as well as decreasing its deformations upon imposed loads.